Investigation of aqueous and organic co-solvents roles in fabricating seawater reverse osmosis membrane - Li, Can; Zhao, Yali; Lai, Gwo Sung; Wang, Rong (Journal of membrane science, 2022)
The addition of co-solvents in aqueous or organic phases of interfacial polymerization is a feasible strategy to tune the performance of aromatic polyamide (PA) thin-film composite (TFC) membrane for brackish water desalination, however, limited progress has been made in developing co-solvent-tailored seawater reverse osmosis (SWRO) membrane. Herein, SWRO membranes were prepared by adding various types of aqueous and organic co-solvents to reveal their impacts on the formation of the PA crumples. It was found that the aqueous/organic co-solvents affected the solubility parameter distance and interfacial tension between two immiscible phases, facilitating the diamine diffusion rate and resulting in a significant change in PA structure. The PA layer with modulated microstructure and varied surface features such as widened void structure, rougher surface, better wettability, and controlled cross-linking degree can be derived from the high interfacial instability that existed between the co-solvent and initial PA film due to the close mutual affinity. Besides, the additional polyvinyl alcohol coating layer atop the PA membrane successfully further enhanced the membrane selectivity. Overall, the mechanistic insights attained in this study revealed the relationship of diamine diffusion, physicochemical properties of PA layer and membrane separation performance for co-solvent-assisted membrane fabrication to render resultant SWRO membrane with more comparable permselectivity. The optimized TFC-SWRO membranes exhibited pure water permeability of 2.2 and 3.2 L m−2 h−1 bar−1 upon the assistance of aqueous and organic co-solvents, respectively, while maintaining excellent NaCl rejection of approximately 99% under seawater desalination tests. [Display omitted] ✓Aqueous or organic co-solvents were used aiming to flexibly design high-performance SWRO membrane.✓The synergistic impacts of solubility parameter and interfacial tension were established to elucidate diamine diffusion behavior.✓The relationship of “monomer diffusion - structure property - separation performance” was elaborated.✓The formation of a PVA coating layer enhanced the selectivity of co-solvent-assisted SWRO membrane.